Navigating Non-Immune Hemolytic Anemia Membranopathy: Definitions to Clinical Strategies - Zahira, Lu'lu Al Fatina; Madani , Ayda Fitri; Kamilah , Nilam Nurmilatun; Amany , Zhafirah; Mario , Andina Nabilah; Amaliya , Annisa Risqi; Makbul , Ini Hidayat; Zakiyyah , Luthfi; Pramudya , I Nengah Andra Putra; Putra , Made Raditya Arhya (Jurnal Biologi Tropis, 2024)
Anemia may arise from increased destruction of erythrocytes, blood loss, or impaired erythropoiesis, as indicated by diminished levels of red blood cells (RBCs) or hemoglobin. Hemolytic anemia involves accelerated RBC lysis that surpasses the bone marrow's compensatory capacity (approximately 120 days) and is categorized into immune and non-immune types. Non-immune hemolytic anemia is primarily hereditary, comprising enzymes, hemoglobinopathies, and membranopathies. This literature review specifically examines non-immune hemolytic anemia membranopathies, detailing their definitions, classifications, etiologies, pathophysiologies, diagnostics, and management. A thorough literature search was conducted using books, reviews, and case studies. Membranopathies are divided into structural defects, such as hereditary spherocytosis (HS) and hereditary elliptocytosis (HE), and altered membrane transport functions, including hereditary stomatocytosis and hereditary xerocytosis. Common symptoms include fatigue, weakness, jaundice, and dark urine, diagnosed through hematological tests and genetic analysis. Management is primarily supportive, involving blood transfusions and folic acid supplementation, with splenectomy recommended for severe cases. A comprehensive understanding of the pathophysiology of these hereditary conditions is critical for accurate diagnosis and effective treatment, underscoring the importance of continued research into novel therapeutic approaches.